Research and development of polyurethane icephobic composite coatings - Memon, Halar (2021)
Ice accretion over critical engineering structures could lead to costly hazards, and ice prevention is an energy-intensive activity, thus making the applications complicated and inefficient. A more promising and specific strategy is to deploy passive ice protection approaches such as durable coatings that allow the super-cooled droplets to slide off before icing (anti-icing), or that detaches the developed ice completely (de-icing). The main aim of this project was to research and develop new types of polyurethane-based icephobic coatings for potential applications in the aerospace and wind energy industries. The experimental work was planned to offer balanced research outputs on the fundamental aspects of icephobicity studies and to impart the acquired knowledge for the fabrication and investigation of novel durable icephobic materials/surfaces.